2015
DOI: 10.7755/fb.113.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of yield-per-recruit and spawning-biomass-per-recruit models to bias and imprecision in life history parameters: an example based on life history parameters of Japanese eel (Anguilla japonica)

Abstract: Abstract-Yield-per-recruit and spawn ing-biomass-per-recruit models, are commonly used for evaluating the status of a fishery. In practice, model parameters are themselves usually estimates that are subject to both bias (uncertainty in the mean) and imprecision (uncertainty in the standard deviation). Using Monte Carlo simulation with data for female Japanese eel (Anguilla japonica) from the Kao-Ping River in Taiwan, we examined the sensitivity of such models to different degrees of bias and imprecision in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the case of the E. coioides we observed that differences in reproductive tactics between Saudi and Emirati waters went as far as to imply a reversal of sex change (Lin et al ., ). Therefore, conservation and management plans for C. bajad in The Gulf should take observed spatial differences in reproductive traits into consideration, especially when using biological reference points related to spawning biomass (Lin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the E. coioides we observed that differences in reproductive tactics between Saudi and Emirati waters went as far as to imply a reversal of sex change (Lin et al ., ). Therefore, conservation and management plans for C. bajad in The Gulf should take observed spatial differences in reproductive traits into consideration, especially when using biological reference points related to spawning biomass (Lin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect estimates of biological reference points may be derived if uncertainty in parameters is ignored. Consequently, conclusions about the status of fish stock will be inaccurate (Helser et al, 2001;Chen and Wilson, 2002;Lin et al, 2015). Quantifying uncertainty in assessment results can enhance decision making for fishery resource management and help determine the best harvest strategies (Gavaris, 1993;Doll et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A coefficient of variation (CV) or standard deviation (SD) is often specified for a subset model according to the available knowledge of parameter uncertainty (e.g., Chen and Wilson, 2002;Grabowski and Chen, 2004;Jiao et al, 2005;Chang et al, 2009). The estimated SDs from the observed data can also be used to introduce random errors (Lin et al, 2015). For correlated parameters, random errors can be introduced using the estimated standard errors and the correlation (Hart, 2013), and the covariance matrix constructed by the estimated SDs and the correlation (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several fishing mortality rate (F)-based biological reference points (BRPs) derived from per-recruit analysis have been used to evaluate whether the YPR is optimum or the SSB/R is sufficient for the population to persist. It also provides fisheries managers with the ability to develop harvest policies (Aprahamian et al 2006;Lin et al 2015;Huo et al 2015). The BRPs usually appear in three forms: targets (target reference points, TRPs), thresholds (threshold reference points, ThRPs) and limits (limit reference points, LRPs).…”
Section: Introductionmentioning
confidence: 99%
“…However, point estimates present only the most possible values, whereas a wide range of values and alternative models may exist. Ignoring uncertainties in biological parameters in per-recruit analysis may yield an incorrect estimation of BPRs, and consequently, the estimation of the fish stock status could be misleading (Chen and Wilson 2002;Lin et al 2015). Caddy (1993) suggested that the imprecision or uncertainty should be taken into consideration when a per-recruit analysis is developed.…”
Section: Introductionmentioning
confidence: 99%